Hidden Stores of Organic Matter in Northern Lake Ice: Selective Retention of Terrestrial Particles, Phytoplankton and Labile Carbon. Issue 8 (5th August 2021) - Imbeau, Elise; Vincent, Warwick F.; Wauthy, Maxime; Cusson, Mathieu; Rautio, Milla
Abstract: Around 50% of the world's lakes freeze seasonally, but the duration of ice‐cover is shortening each year and this is likely to have broad limnological consequences. We sampled freshwater ice and the underlying water in 19 boreal and polar lakes to evaluate whether lake ice contains an inoculum of algae, nutrients, and carbon that may contribute to lake ecosystem productivity. Boreal and Arctic lakes differed in ice duration (6 vs. >10 months), thickness (70 vs. 190 cm), and quality (predominantly snow ice vs. black ice), but in all lakes, there were consistent differences in biological and biogeochemical composition between ice and water. Particulate fractions were often more retained while most dissolved compounds were excluded from the ice; for example, the ice had more terrestrial particulate carbon, measured as fatty acid biomarkers (averages of 1.1 vs. 0.3 µg L −1 ) but lower dissolved organic carbon (2.2 vs. 5.7 mg C L −1 ) and inorganic phosphorus concentrations (4.0 vs. 7.5 µg C L −1 ) than the underlying water. The boreal ice further had three times higher chlorophyll‐ a, than the water (0.9 vs. 0.3 µg L −1 ). Of the dissolved fractions, the contribution of protein‐like compounds was higher in the ice, and this in all lakes. These labile compounds would become available to planktonic microbes when the ice melts. Our results show that freshwater ice has an underestimated role in storage and transformation in the biogeochemical carbon cycle of ice‐covered lake ecosystems. Plain Language Summary: Winter ice cover of 1–2 m thickness can comprise 20%–70% of the total lake depth in boreal and Arctic lakes. While sea ice is known to contain substantial quantities of carbon and organisms that at ice melt contribute to biological production in the underlying water column, little is known about the composition of lake ice and its role in storage of organic carbon. Our analyses of 19 boreal and Arctic lakes revealed large but different stores of organic material in lake ice versus the underlying water. The ice inclusions were composed predominantly of particulate materials, but also of dissolved materials dominated by biolabile compounds that would likely stimulate metabolic pathways and aquatic food webs when they are released into the water at ice melt. This study underscores the pressing need for greater attention to winter as the dominant season at northern latitudes, and to the consequences of rapid contraction of lake ice on microbial and whole lake production. Key Points: Ice covers northern lakes for much of the year and has biogeochemical properties that differ from those in the underlying water Boreal and Arctic lake ice contains large stocks of particulate material composed of detritus, bacteria, and a subset of lake phytoplankton Dissolved organic matter in the ice is dominated by biolabile compounds that may stimulate microbial production at ice‐off